Meta-analytic structural equation modeling (MASEM) analysis of athlete well-being in South Korea - Seongwoo Daniel Seo; Junghoon Huh (Social Sciences and Humanities Open)
Athlete well-being has emerged as a critical concern in South Korea, where early specialization, authoritarian coaching practices, and academic exclusion remain deeply embedded in elite sport systems. This study employed meta-analytic structural equation modeling (MASEM) to synthesize findings from 51 empirical studies and examine how psychological, physical, and social variables interact to shape athlete well-being. Utilizing a two-stage MASEM framework alongside confirmatory factor analysis (CFA), the results revealed that psychological and subjective well-being function as key levers for enhancing athlete outcomes, with physical well-being acting as a central mediating factor. Social support consistently showed significant positive associations across all domains of well-being. Conversely, performance pressure, constrained autonomy, and limited educational access were linked to distress, burnout, and maladjustment following retirement. The final model demonstrated excellent fit and theoretical coherence, integrating core tenets from Self-Determination Theory and ecological systems frameworks. These findings underscore the necessity of embedding well-being into the structural fabric of sport—through reforms in coaching education, investment in mental health infrastructure, and athlete-centered development policies. Future research should adopt longitudinal designs and broaden subgroup representation to inform more inclusive and context-sensitive care models for athletic populations.